Alternative Lead ECG Placements - Morales‐Arteaga, José Luis; Meghdadi, Amin; Wu, Derek; Bhuiyan, Abdullah; Langleben, Nicole; Burak, Cengiz; Wilson, Emily; Pellerito, Ashley; Aristizábal, David; Razzaghi, Keanu; Farina, Juan Maria; Gupta, Shyla; et al. (Wiley, 2026)
Electrocardiography (ECG) is a critical diagnostic tool for identifying cardiac conditions. While standard lead positions are widely used to ensure diagnostic accuracy, alternative lead placements have been developed to address specific clinical scenarios. These alternative configurations can overcome physical or technical challenges, enhance rhythm assessment, improve signal quality, and provide greater specificity for certain conditions, ultimately enabling more personalized diagnostic strategies. This paper examines the clinical significance of alternative ECG lead positions, highlighting their advantages, limitations, and potential applications in various clinical settings. ©The authors ©Wiley.
Keywords: Arrhythmia; ARVD; Brugada; Diagnosis; Electrocardiography; Ischemia; Lead